Performance evaluation of energy aware QoS-enabled routing protocol for wireless mesh networks. (7th December 2022) - Rao, Y. Mallikarjuna; Subramanyam, M.V.; Prasad, K. Satya
This paper proposes an energy aware routing protocol for wireless mesh network (WMNs). In such applications the mesh nodes may not expect the fixed power supply connections for their normal operation. Hence, mesh nodes may rely on ambient energy. In such untenable cases, we require energy aware routing protocols to prevent deterioration of the network performance due to power outages of the nodes. This paper proposes an energy aware QoS-enabled routing (EAQER) protocol based on the node weight and path preference probability. The EAQER is analysed and shown superior performance compared to baseline routing protocols in terms of route request messages, route reply messages, average throughput, end to end delay, jitter, and packet delivery ratio.